Yogurt Products Fortified with Microwave-Extracted Peach Polyphenols - Athina Theocharidou; Evdoxios Psomas; Antonios Koliouskas; Christos Ritzoulis (Gels, 2023)
Pectin and polyphenols have been obtained from choice peach flesh using microwave extraction, with the resulting extracts used in functionalizing strained yogurt gels. A Box-Behnken design was utilized in order to co-optimize the extraction process. Soluble solid content, total phenolic content, and particle size distributions were measured in the extracts. Extraction at pH 1 yielded the highest phenolic content, while increases in the liquid-to-solid ratio resulted in a decrease in soluble solids and an increase in particle diameter. Selected extracts were then incorporated into strained yogurt, and the resulting gel products were assessed for color and texture over a two-week period. All samples were darker and had more red tones than the control set yogurt, while exhibiting less yellow tones. The cohesiveness of all samples remained stable over the gels’ aging of two weeks (break-up times always remaining within 6 s and 9 s), which is close to the expected shelf-life of such products. The work required for the deformation of most samples increases with time, indicating that the products became firmer due to the macromolecular rearrangements in the gel matrix. The extracts obtained with the highest microwave power (700 W) give less firm samples. This was due to the microwave-induced loss of conformation and self-assembly of the extracted pectins. The hardness of all samples increased over time, gaining from 20 to 50% of the initial hardness due to the rearrangement of the pectin and yogurt proteins over time. The products with pectin extracted at 700 W were again exceptions, losing hardness or remaining stable after some time. Overall, this work combines the sourcing of polyphenols and pectin from choice fruit; it uses MAE for isolating the materials of interest; it mechanically examines the resulting gels; and it performs all the above under a specifically-set experimental design aiming towards optimizing the overall process.